2017
DOI: 10.7243/2055-091x-4-9
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological changes in the liver and thyroid of mice (Mus musculus) caused by the acaricides: fipronil and thymol

Abstract: The control of tick Rhipicephalus (Boophilus) microplus, that has the cattle as preferential host, has been performed using products based on different chemical substances. However, the indiscriminate use of these products has caused the selection of resistant populations and damages to the environment, contaminating the soil and water. Tickcides, like fipronil (synthetic chemical) and thymol (natural chemical), are applied on cattle through aspersion, causing the death of the ectoparasites. Nevertheless, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Also, the inflammation in the liver tissue may be caused by hypoxia. NaNO 2 causes a mismatch between the supply and demand of oxygen, causing a surge in ROS production that mediates inflammation [58,60]. During hypoxiation, HIF-1α is overexpressed and translocated to the nucleus to bind with the HIF-1β and its cofactor p300/CBP.…”
Section: Veterinary Medicine Internationalmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the inflammation in the liver tissue may be caused by hypoxia. NaNO 2 causes a mismatch between the supply and demand of oxygen, causing a surge in ROS production that mediates inflammation [58,60]. During hypoxiation, HIF-1α is overexpressed and translocated to the nucleus to bind with the HIF-1β and its cofactor p300/CBP.…”
Section: Veterinary Medicine Internationalmentioning
confidence: 99%
“…e HIF aims to make the cell more glycolytic and produce ATP efficiently, hence producing lactate that enhances inflammation by boosting interleukin-6 and interleukin-23 from macrophage and succinate activates the macrophages [57]. e accumulation of macrophage around the portal area and in the parenchymal hepatocytes is associated with cells' mechanism to eliminate toxic materials to preserve the normal metabolic activities [60].…”
Section: Veterinary Medicine Internationalmentioning
confidence: 99%
“…Along with the steatosis observed in the liver of rabbits exposed to afoxolaner, the onset of cytoplasmic vacuolation around the hepatocyte nucleus was noted. Previous work by Cunha et al (2017) and Roma et al (2012) showed the occurrence of cytoplasmic vacuolation, including around the nucleus in the liver of mice ( Mus musculus ) due to the exposure to synthetic acaricides fipronil, thymol, and permethrin, which could suggest a strategy of hepatocyte preservation in response to the presence of the toxic element in the tissue. In other words, this vacuolation would be removing damaged organelles or even certain regions of the cytoplasm that were altered by the presence of the toxic element, sheltering them in vacuoles that would later be digested and/or eliminated, thus preserving the content that was still intact in the cytoplasm.…”
Section: Discussionmentioning
confidence: 94%
“…However, despite the efficiency of esters as acaricides, little is known about their effects on non-target organisms. Many studies, including those by Cunha et al (2017) , Sodelli et al (2022) , and Vieira et al (2006) , highlighted that these compounds can be toxic to both hosts and non-target organisms, despite their potency as acaricides. Synthetic chemical-based acaricides, such as afoxolaner, have gained prominence in the veterinary market.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation